Espermatogênese no lambari-do-rabo-amarelo astyanax altiparanae: Uma análise histológica com ênfase aos tipos espermatogoniais e espermático - Rodrigues, Maira da Silva [UNESP]; de Siqueira-Silva, Diógenes Henrique [UNESP]; Postingel Quirino, Patrícia [UNESP]; Ninhaus-Silveira, Alexandre [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP] (Boletim do Instituto de Pesca, 2015)
This study aimed to detailed description of the characteristics of the different germ cell types found in Astyanax altiparanae during spermatogenesis. In this purpose, testes from 25 adult male’s specimens of A. altiparanae were sampled and submitted to the usual techniques for light microscopy. Based on nuclear shape, chromatin condensation, nucleoli quantity and cell size were identified four spermatogonial types: type A undifferentiated (Aund.*); type A undifferentiated (Aund.); type A differentiated (Adif.); and type B spermatogonia. Spermatocytes were observed in different phases of meiosis (leptotene/zygotene/pachytene and diplotene), metaphase I and II and secondary spermatocytes, being distinguish mainly by their chromosomal organization inside the nucleus. Were also identified three different types of spermatids, which were named as initial, intermediate and final, which can be differentiated by increase in nuclear condensation and spacing among cells inside the cysts, possibly by flagella arise and reduction in nuclear diameter. Thus, this study contribute to a better understand of spermatogenesis in this and other fish species.
Spermatogenesis in the yellowtail tetra astyanax altiparanae: A histological analyses with emphasis to spermatogonial and spermatid types
Keywords: Fish reproduction; Germ cells; Spermiogenesis; Testis morphology